Estudo de ciclos de adsorção/dessorção do antibiótico ciprofloxacina em coluna de leito fixo empacotada com a resina catiônica SupergelTM SGC650H - Staudt, Junior (2019)
Pharmaceutical compounds are considered environmental problems due to their resistance to the conventional treatments used for wastewater and their consequent presence in the environment, evidenced by numerous recent studies. Techniques involving the mass transfer as adsorption have been tested to the removal of these compounds. However, woks that contemplate the regeneration of the adsorbents by adsorption and desorption cycles are scarce in the literature. In this sense, the aim of this present work is to assess Ciprofloxacin (CIP) adsorption/desorption cycles in a fixed bed column packed with cationic resin SupergelTM SGC650H. Preliminary desorption tests by using different HCl concentrations as eluent agents and adsorption experiments with resin previously treated with these same solutions were carried out in closed-batch system (CBS) to determine the best eluent condition. Physico-chemical characterization tests were performed for virgin and HCl-treated resin, evidencing changes on the resin structure and functional groups caused by the acidic eluents. The preliminary results showed that the HCl concentration of 2 mol L-1 provided both the ciprofloxacin desorption efficiency from the resin and the improvement of the resin’s adsorption capacity. Therefore, this eluent concentration was applied for the further equilibrium experiments in CBS. A phenomenological mathematical modeling was employed to the kinetic and equilibrium desorption data obtained in CBS. The equilibrium data were well described by the Langmuir isotherm model, providing the estimation of the parameters q_max=503,36 mg g-1 and K=5,98 ×10-4 L mg-1, for maximum adsorption capacity and Langmuir affinity constant, respectively. Regarding the kinetic modeling in batch system, the external diffusion was identified as the desorption rate-limiting step, with an estimated kinetic mass transfer coefficient of k_f= 25.7426 h-1. Based on the estimated parameters from independent CBS experiments, the model was able to adequately predict the desorption kinetic behavior in fixed bed column. Thereafter, adsorption/desorption cycles were performed in fixed bed column, and evidenced that the resin capacity was not altered for three experimental cycles. Besides, the mathematical model proposed was able to adequately described both adsorption and desorption steps of the cycles. Overall, the results showed that the HCl eluent solution of 2 mol L-1 was efficiently applied to the regeneration of the resin, due to the high desorption efficiency combined with the activation of the adsorbent. In addition, it was observed that the resin can be employed for three cycles without losing its adsorption capacity. Furthermore, the present work provided a robust and predictive mathematical model of the desorption process, considering equilibrium, kinetic and mass transfer parameters, which could support the design and the scale up of industrial level equipment.